Nursing Practice to Support People Living With HIV With Antiretroviral Therapy Adherence: A Qualitative Study - Rouleau, Geneviève; Richard, Lauralie; Côté, José; Gagnon, Marie-Pierre; Pelletier, Jérôme (The Journal of the Association of Nurses in AIDS Care, 2019)
Antiretroviral therapy (ART) management is a core competency for nursing practice in HIV as documented in best practice guidelines. Nurse-led interventions are effective in fostering ART adherence in people living with HIV (PLWH). However, these evidence-based interventions and professional expectations pertaining to these guidelines do not reflect current practice, nor do they expose the challenges faced by nurses. We conducted a qualitative exploratory study with nurses to explore their professional practices in the context of ART adherence. Sixteen nurses participated in data collection: nine in a focus group and seven in individual interviews. We identified four themes: building a therapeutic relationship with PLWH as a foundation of HIV nursing care; nursing activities to support PLWH with ART adherence; challenges faced by nurses providing ART-related care; and resource mobilization supporting nursing practice development in ART management and HIV care. Aspects of HIV nursing practice need to be strengthened to enhance best practice care, such as managing powerlessness in the context of ART nonadherence.This is an open-access article distributed under the terms of the Creative Commons Attribution-Non Commercial-No Derivatives License 4.0 (CCBY-NC-ND), where it is permissible to download and share the work provided it is properly cited. The work cannot be changed in any way or used commercially without permission from the journal.